The absence and importance of operando techniques for metal-free catalysts - Yuan, Yifei (2020)
Operando characterization techniques have played a crucial role in modern technological developments. In contrast to the experimental uncertainties introduced by ex situ techniques, the simultaneous measurement of desired sample characteristics and near-realistic electrochemical testing provides a representative picture of the underlying physics. From Li-ion batteries to metal-based electrocatalysts, the insights offered by real-time characterization data have enabled more efficient research programs. As an emerging class of catalyst, much of the mechanistic understanding of metal-free electrocatalysts continues to be elusive in comparison to their metal-based counterparts. However, there is a clear absence of operando characterization performed on metal-free catalysts. Through the proper execution of operando techniques, it can be expected that metal-free catalysts can achieve exceptional technological progress. Here, the motivation of using operando characterization techniques for metal-free carbon-based catalyst system is considered, followed by a discussion of the possibilities, difficulties and benefits of their applications.